Consent in the law - Beyleveld, Deryck (Legal theory today., 2007)
In a community that takes rights seriously, consent features pervasively in both moral and legal discourse as a justifying reason: stated simply, where there is consent, there can be no complaint. However, without a clear appreciation of the nature of a consent-based justification, its integrity, both in principle and in practice, is liable to be compromised. This book examines the role of consent as a procedural justification, discussing the prerequisites for an adequate consent -- in particular, that an agent with the relevant capacity has made an unforced and informed choice, that the conse.